Покарання та його призначення за злочини, що вчиняються через необережність : автореф. дис. - Новохатська, Д. В.; Novokhatska, D. V.; Новохатская, Д. В. (Харків, 2018)
Дисертація становить систематизацію знань про оптимальну караність необережних злочинів та раціоналізацію заходів кримінально-правового впливу щодо осіб, які вчинили такі злочини. У дослідженні проаналізовано сучасний стан теорії кримінального права щодо розробки питань караності злочинів, які вчиняються через необережність, закладено методологічні засади оцінки злочину як необережного, узагальнено наукові підходи щодо практичного досягнення мети покарання за необережні злочини. Визначено, які види заходів кримінально-правового впливу варто визнати доцільними для досягнення мети покарання за необережні злочини. На підставі результатів дослідження розроблено низку рекомендацій щодо вдосконалення змісту кримінального законодавства та практики його застосування за злочини, що вчиняються через необережність.

The research describes the systematization of a knowledge about the optimal punishability the negligent crimes and the rationalization of the criminal legal measures in relation to the persons, who committed that crimes. It has been stated a conclusion about the availability three basic concepts of a legal influence in relation to the subjects of the negligent crimes in the world law science. It has been grounded the point of view that the bent of a lawmaker to provide the deprivation of freedom in the sanctions more than 80% negligent crimes is the rudiment of a retributive conception of a nature a criminal punishment. In the thesis was realized the prognosis of development the punishability the negligent crimes, in according to which a specific weight of a deprivation of freedom in sanctions the corresponding norms will be reduce at the expense of more wide application the punishments, that non-connected with the isolation from society. On the ground the negative criminological experience the application to negligent perpetrators the long-term periods deprivation of freedom it is suggest in the capacity of a guideline for criminal policy of a state the observance a principle priority isolation from occupation over isolation from society. It is suggest to make less public inflexible character norms of procedural legislation that currently in force in criminal process on the ground the agreements to negligent crimes, so long as subject of the grave negligent crime must have the possibility of a reduced criminal procedure on the ground the agreement on guilt acceptance, if the victim isn’t contradict that. The writer of this dissertation has improved the scientific views about a reasonability to provide in the Criminal Code of Ukraine deprivation of right to hold a concrete post or to engage a concrete profession on the long-term periods or perpetual. It is reinforce the arguments that for punishment for the negligent crimes more than for intention crimes has inherent tendency of depenalization (exemption from criminal liability, exemption from serving one’s sentence, application the sanctions that are alternative to deprivation of freedom etc.). The thesis has elaborated the scientific views about an elimination the mulct and the correctional works from the sanctions for the negligent crimes, so long as an application by the states these sorts of punishment is contradicting to compensatory function of the criminal law.

Диссертация представляет собой систематизацию знаний об оптимальной наказуемости неосторожных преступлений и рационализации мер уголовно-правового воздействия на лиц, совершивших такие преступления. В исследовании проанализировано современное состояние теории уголовного права относительно разработки вопросов наказуемости преступлений, совершаемых по неосторожности, заложены методологические основы оценки преступления как неосторожного, обобщены научные подходы к практическому достижению цели наказания за неосторожные преступления. Определено, какие виды мер уголовно-правового воздействия следует признать целесообразными для достижения цели наказания за неосторожные преступления. На основании результатов исследования разработан ряд рекомендаций по усовершенствованию содержания уголовного законодательства и практики его применения за преступления, совершаемые по неосторожности.
Автореферат дисертації на здобуття наукового ступеня кандидата юридичних наук (доктора філософії)
Punishment and him imposition for the crimes are committed by negligence
Новохатська, Д. В. Покарання та його призначення за злочини, що вчиняються через необережність : автореф. дис. ... канд. юрид. наук : 12.00.08 / Д. В. Новохатська; МВС України, Харк. нац. ун-т внутр. справ. - Харків, 2018. - 18 с.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Україна. Ukraine. Украина; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 12.00.08; покарання; мета покарання; види покарань; призначення покарання; необережний злочин; необережність; злочинна самовпевненість; злочинна недбалість; наказание; цель наказания; виды наказаний; назначение наказания; неосторожное преступление; неосторожность; преступная самоуверенность; преступная небрежность; punishment; purpose of punishment; sorts of punishment; imposition of punishment; negligent crime; carelessness; criminal presumption; criminal negligence